The Contemporary Role of Photodynamic Therapy in the Treatment of Pachychoroid Diseases - Lawrence P. L. Iu; Ho Yan Chan; Mary Ho; Frank H. P. Lai; Andrew C. Y. Mak; Raymond L. M. Wong; Alvin L. Young (Journal of Ophthalmology)
Recent advances in retinal imaging technology have improved our understanding in the pathogenesis and evolvement of various chorioretinal diseases. Central serous chorioretinopathy and polypoidal choroidal vasculopathy are now recognized to belong to the same spectrum of disorders known as pachychoroid diseases. Pachychoroid diseases have similar pathogenesis pathway and common characteristics of thickened choroid, dilated outer choroidal vessels, and thinning of choriocapillaris. More disease entities have been identified to belong to this disease spectrum. Photodynamic therapy can induce choroidal hypoperfusion, remodeling of abnormal choroidal vessels, and reduction of choroidal congestion. It is known to be an effective treatment for chronic central serous chorioretinopathy and polypoidal choroidal vasculopathy. Many new studies are being performed to investigate its efficacy in other pachychoroid diseases. In this review, we provided an overview of the rationale, efficacy, and treatment strategies of photodynamic therapy in different pachychoroid diseases and discussed its role in the management along with other treatment modalities with most updated clinical evidence.